Chromosome abnormality incidence in fetuses with cerebral ventriculomegaly. (July 2014) - Gezer, C.; Ekin, A.; Ozeren, M.; Taner, C. E.; Ozer, O.; Koc, A.; Bilgin, M.; Gezer, N. S.
Abstract Ventriculomegaly (VM) is a marker of aneuploidy and warrants a detailed examination of fetal anatomy. Chromosomal abnormalities worsen the fetal and neonatal prognosis significantly and karyotyping of fetuses is critically important when accompanying anomalies are detected. Here, we report the genetic results of 140 fetuses with isolated and non-isolated VM detected during a second trimester ultrasound examination followed by invasive in utero diagnostic procedures for karyotyping. VM was diagnosed in seven (5%) fetuses with abnormal karyotype and the chromosomal abnormality incidence was higher in severe VM (6.8%) than mild (4.2%). Higher chromosomal abnormality rates were detected when VM was isolated (8.6%), rather than associated with any anomaly (3.8%). These results suggest that karyotype analysis should be offered to all patients with any degree of VM, regardless of its association with structural anomalies.